Neighborhood socioeconomic status and postpartum depression among commercial health insurance enrollees: a retrospective cohort study - Onur Baser; Lauren Isenman; Erdem Baser; Wenjing Li; Burhan Cigdem (BMC Pregnancy and Childbirth, 2024)
Abstract Background Postpartum depression (PPD) is a prevalent psychological condition. Although the effect of obstetrical and maternal complications on PPD are well described, the impact of neighborhood socioeconomic status (SES) on PPD is relatively unexplored. Objectives This study examined the relationship between neighborhood SES score and PPD. Methods A summary SES measure for each U.S. zip code was constructed using income, education, and occupational 2021 Census data and linked to national commercial claims for 2017–2023. PPD status using diagnosis codes at outpatient and inpatient visits, and prescription drug use 3, 6, 9, and 12 months postpartum, were determined. Multivariate analysis controlled for potential confounders. Results PPD prevalence in commercial claims was 11.48%. Patients with PPD had higher rates of obstetrical (OR: 1.555, p < .0001) and maternal complications (OR: 1.145, p < .0001), and more lifestyle risk factors (OR: 1.113, p < .0001). Comorbidity scores were higher for patients with PPD. Controlling for age and clinical factors, living in a disadvantaged neighborhood was associated with an increased incidence of PPD (OR: 1.137, p < .0001). Limitations Claims data may include potential inaccurate coding of diagnoses/procedures. Clinical information is limited to conditions and treatments defined by ICD-10-CM codes. Area-based SES measures inevitably misclassify people on both ends of the socioeconomic spectrum (this misclassification is random; direction of bias is known). Conclusions The inverse and significant effect of area-based high SES on PPD rates demonstrates that preventive efforts may require interventions focusing on both the patient and the lived environment.